Living for the City Social Change and Knowledge Production in the Central African Copperbelt - Larmer, Miles (Social Sciences, 2021)
A holistic understanding of the diverse history of the cross-border Central African Copperbelt, considered here as a single region, this study integrates neglected aspects of Copperbelt history including women, non-mining communities, informal settlements and urban agriculture into the region's history.